Diffusion-weighted imaging and diffusion tensor imaging of the heart in vivo: major developments - Mazur, Weronika; Krzyżak, Artur; Hennel, Franciszek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Diffusion-weighted magnetic resonance imaging (DWI) is a powerful diagnostic tool. Contrast in DWI images is dictated by the differences in diffusion of water in tissues, which depends on the tissue type, hydration and fluid composition. Therefore DWI can differentiate between hard and soft tissues, as well as visualize their condition, such as edema, necrosis or fibrosis. Diffusion tensor imaging (DTI) is a DWI technique which additionally delivers information about the microstructure. In cardiovascular applications DWI/DTI can non-invasively characterize the acute to chronic phase of the area at risk and microstructural dynamics without the need to use contrast agents. However, cardiac DWI/DTI differs from other applications due to serious anatomic and technologic challenges. Over the years, scientists have stepped up overcoming more and more advanced obstacles associated with complex 3D myocardial motions, breathing, blood flow and perfusion. The aim of this article is to review milestone technologic advances in DWI/DTI of the heart in vivo. The discussed development begins with the adjustment of the diffusion imaging block to the electrocardiogram-based most quiescent phase, next considers different pulse sequence designs for first-, second- and higher-order motion compensation and SNR improvement, and ends up with prospects for further developments. Reviewed papers show great progress in this research area, but the gap between the scientific development and common clinical practice is tremendous. Cardiac DWI/DTI has promising clinical relevance and its addition to routine imaging techniques of patients with heart disease may empower clinical diagnosis.